Detección de Chlamydia trachomatis como agente causal de infecciones genitourinarias en pacientes embarazadas que acuden al Centro de Salud Motupe - Jiménez Merino, Mireya Carolina (2022)
Chlamydia trachomatis is a gram-negative bacterium, a pathogen considered as one of the main etiological agents of sexually transmitted infections (STI), it usually presents symptomatically and asymptomatically in both men and women, during pregnancy it causes premature births, premature rupture of membranes and endometritis, low birth weight in newborns, pneumonia, conjunctivitis, and neonatal death. For this reason, we focused on detecting the presence of Chlamydia trachomatis as a causal agent of genitourinary infections in pregnant patients attending the Centro de Salud Motupe in the province of Loja during the period May-August 2022. This was a quantitative, cross-sectional, and relational study, made up of pregnant patients who presented compatible pictures of genitourinary infections, a survey was applied on factors associated with the pathology and the technique of indirect IgM antiChlamydia trachomatis Elisa for its subsequent relationship through Chi-square. The results showed that 5.8% (n=5) of pregnant women were positive for IgM anti-Chlamydia trachomatis, in addition to finding a statistically significant relationship with early sexual debut with an average age of 14.6 years and the non-use of condoms. Finally, it was concluded that there is the presence of Chlamydia trachomatis in the active phase, with the main risk factors being the beginning of early sexual life and the non-use of condoms; but other factors such as age, genital infection in the pregnant woman, genital infection in the spouse and whether she has a stable partner, although they did not have a statistically significant relationship, cannot be excluded as risk factors